Role of Union Parisahd (UP) For Implementation Social Safety Net Programs (SSNPS) in Rural Bangladesh - Gazi Ibrahim Al Mamun (Asian Studies, 2025)
This study aims to explore the role of UP in implementing SSN programs in rural Bangladesh to reduce poverty. It uses a mixed method approach of research, where three types of research methods, such as questionnaire survey, key informant interview (KII), and observation have been used as well as the data were derived from VGD, OAA and EGPP program beneficiaries, the local public, UP members (former and present), government officials, NGO officials, Bankers and local elites in the program running area of Bangladesh. As per the methods of structured and semi-structured questionnaires, open-ended questionnaires and checklists have been used as data collection tools. The findings show that the UP has performed five functions effectively for the SSN program implementation. However, its activities are ineffective for implementing SSNPs at the rural level of Bangladesh. In this case, corruption, nepotism, disobeying the rules and law, political faction, political pressure on UP, lack of coordination and cooperation of the upazila administration, and lack of transparency and accountability are obstacles to the effective implementation of SSNPs through UP. The findings lead to some recommendations that will give insights to policymakers and professionals engaged in this field.